PENGEMBANGAN MEDIA PEMBELAJARAN PENGOLAHAN DAN PENYAJIAN MAKANAN INDONESIA DENGAN APLIKASI LECTORA PADA SISWA KELAS XI JASA BOGA SMKN 4 KOTA JAMBI - Dewi Rahmayanti (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
The research intended to produce a Lectora Inspire-based learning media and recognize its effectivity on students of Cookery XI Class at SMKN 4 Kota Jambi. It was a type of developing research. The subject was students of Cookery XI Class at SMKN 4 Kota Jambi. The model of the research development referred to ADDIE model by Lee And Owen, which consists of 5 stages, namely: Analysis, Design, Development, Implementation and Evaluation. The method of data collection was observation, interview, questionnaire/ interview guide and documentation. The assessment of video propernesswas validated by media and content experts. The sample of the small class was 15 students and the big class was 30. The technique of data analysis was descriptive statistic. The result of the development research was a Lectora Inspire-based learning media properly used by students of Cookery XI Class not only in term of its suitability with the syllabus and lesson plan but also content and media aspects. The validation given by validators from content and media experts stated the properness in the scale of “Very Agree”. It was concluded that the Lectora Inspire-based learning media was usable for learning media. Based on the validation result, the media was tested to a small scale class and reached 91,42% of presentation result which was categorized in the scale of “Very Agree”. It was then tested in a field test with presentation result 89,79% which was categorized in the scale of “Very Agree”. As the result, it was clearly stated that the learning media of Preparation and Presentation of Indonesian Food was properly used as learning media for students of Cookery XI Class at SMKN 4 Kota Jambi.